Kajian Interaksi Wilayah Berbasis Model Gravitasi dan Analisis Ketimpangan Wilayah di Provinsi Sulawesi Tenggara - Fitriani, Fitriani; Nusriah, Asyravil Maolana (Prodi PWK Universitas Tadulako, 2025)
Southeast Sulawesi Province faces inter-regional development challenges due to its geographical diversity, consisting of both mainland and archipelagic area, which creates disparities between regions. This study aims to determine the regional interaction between Kendari City and 16 other regencies/cities and to measure the level of disparity in Southeast Sulawesi Province. The research method used is the gravity model for regional interaction analysis and the Williamson index to measure regional disparity. The results show that South Konawe Regency has the highest interaction index (strength: 1.00) with Kendari City, followed by Konawe Regency (strength: 0.78). The Williamson index value indicates regional disparity between 0.42 and 0.49 (moderate category) over a five-year period. This study implies the need to strengthen integrated transportation infrastructure between regions, particularly through maritime connectivity for archipelagic area, as well as the implementation of local economic diversification based on the comparative advantages of each region.